Factors affecting stigma of epilepsy. Issue 3 (July 2017) - Hassan, Wageeh A.; Elserogy, Yasser M.; Abdelrahman, Ahmed A.; Khalifa, Hosam; Badry, Reda; Hussein, Hussein B.
Abstract : Background: Epilepsy is a common and chronic brain disorder that affects about 50 million people worldwide. The majority of the affected population lives in the low-income regions of the world. Stigma and social marginalization are common to persons with epilepsy. Purpose: The aim of the present study was to evaluate the factors, including personality and psychological illnesses, likely to be influential in enhancing the social stigma of epilepsy. Methods: Data were collected from 102 epileptic adults recruited from the Epilepsy Clinic of Assiut University Hospital in Egypt, with 52 healthy adults included as controls. Clinical information about seizures was obtained from neurologists, and other information was collected from self-completed questionnaires, including those measuring stigma scales. Results: Overall, 65.7% of the people with epilepsy felt stigmatized by their condition and in 17.6% of these the stigma was severe. Multivariate analysis identified experiences of actual discrimination from society; more introverted personalities had a higher degree of depression and anxiety with a low self-esteem, and all dimensions of Quality of Life-36 questionnaire short form were negatively correlated with the social stigma of epilepsy. Conclusion: Factors suggested to have an impact on stigma of epilepsy include seizure-related aspects such as seizure type, frequency, duration of illness, type and number of medications, and EEG changes, and individual-related aspects such as age, sex, residence, occupational status, marital status, educational level, age at seizure onset, and the affection of the quality of life.